PENGELOLAAN ARSIP DAN EFISIENSI KERJA PEGAWAI PADA KANTOR SEKRETARIAT DAERAH KOTA DENPASAR - I Gusti Gde Oka Pradnyana; Chintia Dini Noviani (Forum Manajemen, 2015)
Each office job, eiher government or private always there is saving process,register and mail process with certain system and able to guaranteed. In line withorganization development, hence activities in organization increase so that needsa good file management. If file managed in good hence process of work will faster,cheap, and accurate and success. All of this will make work efficiency increase. Thisstudy aim to find out the efficiency of employee work at local secretariat office ofDenpasar city. Data analysis technique was used simple regression analysis and ttest. Data processing assisted with SPSS for windows version 17,00. From the resultof analysis can be concluded that management of file have positive and significanteffect toward employee work efficiency. It can be seen from simple linear regressionequation that is Y=6,753 + 0,812X. It shows that if management of file increasedhence employee work efficiency will increase too. While probability test obtainedsignificant value is 0,000 too far from alpha value 5% (0,05) so that it have significanteffect. Suggest can be given that management of work file in re-finding of file andwill need extension of file saving room and employee work efficiency especially workdiscipline need improved.